Designing ELF-aware lessons in high-stakes exam contexts - Sifakis, N.; Tsantila, N.; A. Masina; K. Vourdanou (ELT Journal, 2020)
In ELT contexts, the concept of ELF awareness has been proposed as a means of developing the skills, strategies, and overall outlook that learners require to competently participate in ELF interactions. Depending on the teaching context, this can be a demanding process. We discuss the ELF-aware instructional interventions carried out by two practitioners working in high-stakes exam preparation contexts in Greece. These contexts are predominantly Standard English oriented. The interventions described an attempt to put into practice the principles of ELF-aware pedagogy, namely awareness of language and language use, awareness of instructional practice, and awareness of learning. The innovative aspect of these interventions is that they do not run contrary to the curriculum of these high-stakes exam preparation classes. On the contrary, they complement the courseware used in these contexts with authentic audiovisual materials and original metalinguistic activities that boost learners’ self-confidence as ELF speakers and as candidates of these exams.